Lumbar Puncture in the Neonate - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The diagnostic utility of lumbar punctures in neonates was evaluated in the Division of Neonatology, Department of Pediatrics, University of Miami, FL.